The Strategy of Human Resources Development Program for Civil Servants (ASN) through Work Culture Mindset Training in Improving ASN Work Behavior by the Regional Human Resources Development Agency (BPSDMD) of Banten Province - Amelia, Mia; Fauzi, Ahmad; Siregar, Herlina (The Future of Education Journal, 2024)
This study aims to describe (1) the strategy of the Civil Servant Human Resource Development program, (2) the implementation of the work culture mindset training, and (3) the improvement of Civil Servant work behavior after participating in the work culture mindset training. The research method used is a descriptive method with a qualitative approach. The data collection techniques used are interviews, observations, documentation, and literature studies. The data collection methods used are interviews, observations, documentation, and literature studies. The informants in this study consist of the Head of the General Affairs Subdivision, 1 trainer and 10 Civil Servants from the Banten Provincial Government. The results of this study are as follows: (1) The strategy for the Civil Servant Human Resource Development program is carried out through several elements, including the identification of development needs, the preparation of training and development programs, the introduction of continuous training, management and leadership support, performance evaluation and measurement, as well as the use of the latest technology and learning methods. The implementation of the work culture mindset training is carried out based on the results of the development needs identification and program preparation within the human resource development strategy that has been conducted. The implementation of this training consists of several components, such as setting goals, training benefits, training participants, trainers, training schedule, training materials, training facilities, training methods, and training media. After the Civil Servant Human Resource Development program strategy is implemented through work culture mindset training, it has a positive impact, resulting in improvements in work behavior such as the development of cooperative social skills, work quality, positive work habits, and personal presentation or self-control.